Insufficient Iron Improves Pristane-Induced Lupus by Promoting Treg Cell Expansion - Gao, Xiaofei; Song, Yang; Lu, Shuang; Hu, Longyuan; Zheng, Meiling; Jia, Sujie; Zhao, Ming (Frontiers in Immunology, 2022)
Trace element iron affects T cell biology, but the knowledge about the role of iron in regulating Treg cell expansion is limited. Treg cells play an important role in keeping peripheral T cell tolerance, increasing Treg cell expansion is a promising therapeutic method for SLE. Here we showed that iron deficiency promotes Treg cell expansion by reducing ROS accumulation, improving the disease progression of pristane-induced lupus. Increased oxidative stress inhibits Treg cell differentiation by inducing cell apoptosis. Our data suggest that altering iron metabolism promotes Treg cell expansion by preventing oxidation-induced cell death, which may provide a potential therapeutic strategy for SLE.